Business strategy and product development using lean startup: case study at pegasus company - Rizky Mubarak, Muhammad; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2016)
Abstract. Pegasus is a company which operates in gaming industry in Indonesia. Pegasus produces high quality gaming chair for gamers and people who spent most of their time in front of the computers. Pegasus gaming chair significantly reduce body parts pain for people who are sitting for a long time in front of the computer, thus enabling those people to play computer games or sit in front of the computer for a long time. Today, the gaming industry is in uptrends. According to Polygon, The International Dota 2 gaming tournament is watched by more than 20 million people from all around the world and people who play online game in the world has reach more than 1,2 billion people (McWhertor,Michael ,2014). Growth of the game player in Indonesia also grow in a high rate parallel with the industry uptrends. In order to compete in this growing industry and grab its market share, Pegasus need to have business strategy and correct product design that reflect the preference of the customer. The analysis used are internal, external and combination analysis. After the internal external analysis is done, the factors that Pegasus are lacking and what can be improved are identified. TOWS matrix is a tool that is used to develop strategic options from a combination of external and internal analysis (Doherty, B, 2009).  Data that are gathered from the internal and external analysis then is used to formulate business strategy using TOWS Matrix in the combination analysis. The strategies resulted from the analysis are to increase product awareness, create new product line up for different type of customers, create gaming tournaments for additional revenue stream and product exposure, additional distribution channel via online and offline store, and additional international supplier that can provide the product materials with lower cost. According to (Ries, E, 2011) the lean start-up methodology provides an approach in which to create & managing start-up and get the product to the customer’s faster. Lean start-up itself is an approach to new product development. The methodology was utilized in order to develop product based on customer feedback. Data of the improvement to be made that are gathered from the Internal & external analysis with the strategy formed by using TOWS Matrix then are used to improve the business model of Pegasus through its business canvas. The improved business model canvas then is used as a guideline for Pegasus in order to correctly deliver value proposition to the customer and how to manage cost structure and revenue streams. This rapid growth of gaming industry in Indonesia are very good opportunity for Pegasus to capture high number of customer, increasing profit, and also become market leader in gaming chair.  Keywords: Game, Gaming Industry, Gaming Tournament, Gaming chair.